Impact of educational intervention on the best immunization practices among practicing health care professionals in a south Indian city - Juny Sebastian; Gurumurthy Parthasarathi; Mandyam Dhati Ravi (SAGE Publishing, 2021)
Background and Aims: Maintaining the quality and safety of immunization is as important as the efficacy of vaccines in vaccine-preventable diseases (VPD) programs. The aim of this study was to determine the problems associated with different stages of vaccine use and to assess the outcome of an educational intervention on safety and quality use of vaccines among health care providers. Methods: A pilot prospective interventional study was conducted over a period of 2 years at 271 sites in Mysuru, India. The study population was health care professionals (HCPs) involved in immunization and a sample of parents (one per site). A validated questionnaire was used as a study tool. An educational intervention on best immunization practice was conducted for the enrolled HCPs and the impact of the educational intervention was assessed using the study tool after 3 weeks. Results: The total number of the study population was 594 (323 HCPs and 271 parents). Of these, 41.49% were working at community health care facility and 33.13% were enrolled from primary care centers. There were statistically significant improvements in post interventional assessment of all stages of the immunization process including storage ( p −0.001), transportation ( p −0.001), administration ( p 0.001), monitoring and reporting of adverse events following immunization (AEFIs) ( p −0.001), knowledge of AEFIs ( p 0.001), and HCP-parent communication ( p 0.001). AEFI reporting improved by 30% in the post education phase. Conclusion: Continuous education and motivation can result in positive behavioral changes on best immunization practices amongst HCPs involved in immunization, which may help to improve and maintain the safety and quality use of vaccines in immunization centers irrespective of the type of facility.